1987
DOI: 10.1042/bj2480289
|View full text |Cite
|
Sign up to set email alerts
|

Short-term incubation of cardiac myocytes with isoprenaline has no effect on heparin-releasable or cellular lipoprotein lipase activity

Abstract: Heparin (5 units/ml) produced a rapid (5-10 min) release of lipoprotein lipase (LPL) into the incubation medium of cardiac myocytes. Preincubation of myocytes for 30 min with 0.01-10 microM-isoprenaline, 100 microM-forskolin or 500 microM-8-(4-chlorophenylthio)adenosine 3′,5′-cyclic monophosphate did not increase heparin-releasable LPL activity. Incubation with isoprenaline also did not change cellular LPL activity, even though the catecholamine did increase the phosphorylase a activity ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…of 4 x 105 cells/ml, and were incubated at 37°C under 02/CO2 (19:1). The release of LPL into the incubation medium was measured as described previously [14][15][16]. Heparin was added to the myocyte incubation medium to give a final concentration of 5 units/ml, and at various times 1 ml samples were removed and centrifuged for 10 s at 15000 g in an Eppendorf centrifuge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…of 4 x 105 cells/ml, and were incubated at 37°C under 02/CO2 (19:1). The release of LPL into the incubation medium was measured as described previously [14][15][16]. Heparin was added to the myocyte incubation medium to give a final concentration of 5 units/ml, and at various times 1 ml samples were removed and centrifuged for 10 s at 15000 g in an Eppendorf centrifuge.…”
Section: Methodsmentioning
confidence: 99%
“…5 %, v/v) was added to the cultured myocytes in 1 ml ofJoklik medium. After centrifugation, the deproteinized supernatant was neutralized and cyclic AMP was measured by radioassay [16,17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that incubation of cardiomyocytes with Iso for 30 min had no effect on either basal or HR-LPL activity (60). In the present study, incubation with this ␤-agonist was Values are means Ϯ SE for 6 animals in each group.…”
Section: Coronary Luminal Lpl Activity Increases After a Single Dose mentioning
confidence: 53%
“…Thus, even though the majority of enzyme is located in myocytes, vascular endothelial-bound LPL likely determines the rate of plasma lipoprotein-TG clearance (41). Previously, incubation of cardiomyocytes with Iso for 30 min did not change either HR-LPL or cellular LPL activity (60). We have confirmed these findings even after incubation with Iso was prolonged for 1 h. Because cardiomyocytes are quiescent, we extended these experiments to an isolated retrograde perfused heart and demonstrated a similar absence of effect of this ␤-agonist on LPL.…”
Section: Discussionmentioning
confidence: 97%